Effectiveness of mobile phone text messaging in improving glycaemic control among persons with newly detected type 2 diabetes. (December 2019) - Vinitha, Ramachandran; Nanditha, Arun; Snehalatha, Chamukuttan; Satheesh, Krishnamoorthy; Susairaj, Priscilla; Raghavan, Arun; Ramachandran, Ambady
Highlights: To study the utility of text messages on glycaemic control in newly diagnosed diabetes patients. At 24 months, sustained improvement in HbA1c was noted. Improvements in blood pressure, LDL-cholesterol, fasting and 2-hour glucose observed. Abstract: Aims: The aim of the study was to evaluate the effect of text messaging as a tool to improve glycaemic control among newly diagnosed T2D patients in a 2 year period. Methods: This is a multicentric, randomised controlled trial conducted in 2 states of India. The primary outcome was improvement in glycaemia measured by an HbA1c value of ≤7% (53 mmol/mol) with intervention. The secondary outcomes were changes in biochemical, dietary parameters and physical activity. Acceptability of text messages was assessed. Persons having HbA1c value of ≥6.5% (48 mmol/mol) at diagnosis were enrolled. A total of 248 participants with a mean age of 43.3 ± 8.7 years were recruited. Participants in the control group (n = 122) received standard care, the intervention group (n = 126) received customized text messages thrice a week. Both groups received personal advice at the beginning of the study. Results: Baseline characteristics were similar in both groups. At 24 months, both groups showed significant reduction in blood pressure and glycaemic variables in comparison to the baseline values. The intervention group showed significant lowering of LDLc also. Multivariate analysis showed that reduction in HbA1c was associated with intervention. Conclusion: Text messaging can lead to improvement in glycaemic control through personal empowerment and sustained behavioural changes.